2021
DOI: 10.1007/s10639-021-10623-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the e-mentoring-based education program on professional development of preschool teachers

Abstract: The qualification of a preschool teacher is one of the important factors that determine the quality of preschool education. To increase the quality in education, teachers should be equipped with the necessary knowledge starting from pre-service training, and in-service training should support the upgrading of their knowledge. Thus, the aim of this study was to develop an e-Mentoring-Based Education Program (e-MENTE:PT) for preschool teachers and to test its effectiveness on their professional development durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
(35 reference statements)
0
7
0
1
Order By: Relevance
“…Stimulation of personal development stood out in supporting individual growth for teachers. "Programa e-MENTE" Erdoğan et al (2022) In terms of content knowledge, it is observed that the e-MENTE: PT Program has had a significant impact on preschool teachers. Modules related to the recognition and evaluation of the child, learning centers, and the teacher's role, as well as planning, implementation, evaluation, and family participation, have experienced notable improvements.…”
Section: "Monitoreo De Actividades Programadas Y Ejecutadas Del Acomp...mentioning
confidence: 99%
“…Stimulation of personal development stood out in supporting individual growth for teachers. "Programa e-MENTE" Erdoğan et al (2022) In terms of content knowledge, it is observed that the e-MENTE: PT Program has had a significant impact on preschool teachers. Modules related to the recognition and evaluation of the child, learning centers, and the teacher's role, as well as planning, implementation, evaluation, and family participation, have experienced notable improvements.…”
Section: "Monitoreo De Actividades Programadas Y Ejecutadas Del Acomp...mentioning
confidence: 99%
“…Selanjutnya, program e-Mentoring-Based Education Program (e-MENTE:PT) dilaporkan efektif untuk pengembangan profesionalisme guru (Erdoğan et al, 2022). E-MENTE:PT diinstal dalam sebuah sistem aplikasi dimana guru sebagai mentee dapat bekerja dengan mentor satu per satu.…”
Section: Program Pembinaan Dengan Pendekatan Individuunclassified
“…Studies on e-mentoring practices in general report positive outcomes for participating teachers of different subjects (Erdogan et al, 2022;McAleer & Bangert, 2011;Simonsen et al, 2009). For instance, a study conducted by Erdogan et al (2022) examined the impact of an e-mentoring-based education program on in-service preschool teachers' PD in terms of pedagogical content knowledge.…”
Section: E-mentoringmentioning
confidence: 99%
“…Studies on e-mentoring practices in general report positive outcomes for participating teachers of different subjects (Erdogan et al, 2022;McAleer & Bangert, 2011;Simonsen et al, 2009). For instance, a study conducted by Erdogan et al (2022) examined the impact of an e-mentoring-based education program on in-service preschool teachers' PD in terms of pedagogical content knowledge. Using various materials (e.g., e-books, videos, and live lessons) and with the participation of 28 pre-school teachers and nine academics, the content supported the professional knowledge, learning environments and classroom applications of the preschool teachers.…”
Section: E-mentoringmentioning
confidence: 99%
See 1 more Smart Citation